2018
DOI: 10.1155/2018/8515829
|View full text |Cite
|
Sign up to set email alerts
|

Does Adding Silver Nanoparticles to Leukocyte- and Platelet-Rich Fibrin Improve Its Properties?

Abstract: Objectives Leucocyte- and platelet-rich fibrin (L-PRF) membrane can be used in various regenerative treatments. In the case of classical heterologous membrane exposure, microorganisms can be colonized on it and jeopardize the success of treatment. The aim of this study was to compare the antibacterial, mechanical, and histologic characteristics of the L-PRF membrane before and after the addition of silver nanoparticles (SNP). Materials and Method This study was performed on 10 volunteer men aged 25-35 years. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
2
22
6
Order By: Relevance
“…The E‐modulus of the control membranes in the current study was 0.07 MPa and is comparable (Table 4) to the results of one study found in literature., 15 but lower than the results reported in two other studies and higher than a fourth study 16‐18 . The ultimate tensile strength of the control membranes was 0.29 MPa, which is higher than reports of the strength of L‐PRF in multiple other studies 15,17‐19 . The elongation at break of the control membranes in the current study was about 2.8 times their initial length, which is higher, comparable, and lower than three other studies that recorded an elongation of 1.45, 2.17, and ± 3.50, respectively 15,16,19 .…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The E‐modulus of the control membranes in the current study was 0.07 MPa and is comparable (Table 4) to the results of one study found in literature., 15 but lower than the results reported in two other studies and higher than a fourth study 16‐18 . The ultimate tensile strength of the control membranes was 0.29 MPa, which is higher than reports of the strength of L‐PRF in multiple other studies 15,17‐19 . The elongation at break of the control membranes in the current study was about 2.8 times their initial length, which is higher, comparable, and lower than three other studies that recorded an elongation of 1.45, 2.17, and ± 3.50, respectively 15,16,19 .…”
Section: Discussioncontrasting
confidence: 73%
“…In short, the current results of tensile testing are quite similar or differ slightly from results obtained in other studies 15,17‐19 . All previously mentioned studies had different protocols for blood centrifugation and tensile testing though, 15‐19 which makes any comparison difficult (Table 4). The time of blood centrifugation, the g‐force of the centrifuge, the shape of the L‐PRF membrane (rectangular or dog bone shaped) with tensile testing and the crosshead speed of the tensile test have to be taken into consideration.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The third layer (PRP) was carefully separated by pipette and recentrifuged at 1240 rpm for 5 minutes. Then, the plasma layer (top layer) was discarded and the PRP layer (second layer) was collected for intra conduit injection (7,8).…”
Section: Platelet-rich Plasma Preparationmentioning
confidence: 99%